Awake Thoracic Surgery - Pompeo, Eugenio (Bentham Science Publishers, 2012)
Awake thoracic surgery is a new surgical field that is set to expand in the near future. Employing sole epidural or local anaesthesia in fully awake patients renders many thoracic surgical procedures doable with less invasiveness and general anaesthesia related adverse effects can be avoided. This, in turn, facilitates fast track surgery and improves cost-effectiveness of treatment procedures. The book explains issues relevant to awake thoracic surgery including postoperative immunologic and stress-hormone responses, lung volume reduction surgery, pulmonary resections and thymectomy. This Ebook should be useful to readers interested in a comprehensive reference work on this intriguing minimally invasive surgical option.